2021
DOI: 10.1029/2020gl091033
|View full text |Cite
|
Sign up to set email alerts
|

Is Mesospheric Quasi Biennial Oscillation Ephemeral?

Abstract: Inter-annual variability in the state of the equatorial middle atmosphere is dominated by the quasi biennial oscillation (QBO), whose time period ranges from 22 to 34 months with an average period around ∼28 months (Baldwin et al., 2001). The stratospheric QBO (SQBO) in zonal winds maximizes in 27-30 km altitude region whereas the mesospheric QBO (MQBO) maximizes at around 85-90 km altitude (Baldwin et al., 2001). The source mechanism of the QBO, its variability at various temporal scales, and its role in modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
3
1
0
Order By: Relevance
“…(2001) using HRDI observations was approximately 30 m/s. However, further studies using meteor radar observations over equatorial and low latitudes reported significantly smaller MQBO amplitudes ranging from 3.5 to 6 m/s (de Wit et al., 2013; Kumar, 2021; Malhotra et al., 2016), which is consistent with our results. Figure 1c displays the spectrum obtained by the least squares fitting method with the 95% confidence level of the deseasonalized zonal wind which is shown in Figure 1b.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…(2001) using HRDI observations was approximately 30 m/s. However, further studies using meteor radar observations over equatorial and low latitudes reported significantly smaller MQBO amplitudes ranging from 3.5 to 6 m/s (de Wit et al., 2013; Kumar, 2021; Malhotra et al., 2016), which is consistent with our results. Figure 1c displays the spectrum obtained by the least squares fitting method with the 95% confidence level of the deseasonalized zonal wind which is shown in Figure 1b.…”
Section: Resultssupporting
confidence: 92%
“…As shown in Figure 9, the maximum amplitudes of the SQBO were approximately 30 m/s, consistent with the results of previous studies (Baldwin et al., 2001; Ratnam et al., 2008). In previous studies using meteor radar observations over equatorial and low latitude, MQBO amplitudes ranging from 3.5 to 6 m/s were reported (de Wit et al., 2013; Kumar, 2021; Malhotra et al., 2016), which is in line with our results shown in Figure 1b. Hence, the amplitude of the MQBO was much smaller than that of the SQBO.…”
Section: Discussionsupporting
confidence: 93%
“…As the height increases, the responses of BU to QBO30 become stronger again and have peak around ~90 km. This coincides with the mesospheric QBO, which is antiphase with the stratospheric QBO and extends to 30°S-30°N as revealed by High Resolution Doppler Imager observations (HRDI) (Burrage et al, 1996), TIMED Doppler Interferometer observations (Kumar, 2021) and reviewed by Baldwin et al, (2001).…”
Section: 3supporting
confidence: 57%
“…QBO signal can also be seen in the mesosphere, which is anti-phase to the stratospheric QBO due to the selective critical-layer filtering (Baldwin et al, 2001;Burrage et al, 1996;Xu et al, 2007). Recent studies revealed that the mesospheric QBO is a seasonally locked phenomenon and occurs only in vernal equinox when the westward winds enhanced every 2 or 3 years and might be an ephemeral phenomenon (Venkateswara Rao et al, 2012;Kumar, 2021); the ENSO (El Niño/Southern Oscillation) is used to characterized the changes in sea surface pressure and temperature (Domeisen et al, 2019a). It has been reported that the slight change of ENSO can affect global middle and upper atmosphere through the coupling of atmosphere and ocean and wave propagation (Randel et al, 2009;Li et al, 2013;Baldwin and O'Sullivan, 1995;Lin and Qian, 2019); the solar activity can be represented by its radiation flux at 10.7 cm (F10.7), its can influence the atmosphere from upper to below through photon absorption and high energy particle precipitation and ion deposition (Li et al, 2011;Beig et al, 2008;Qian et al, 2019;Venkat Ratnam et al, 2019).…”
Section: Introductionmentioning
confidence: 99%